Diving measurement and analysis of the take-off - Bergmaier, G.; Wettstein, A.; Wartenweiler, J. (First International Symposium on "Biomechanics and Swimming, Waterpolo and Diving", 14-16 September 1970. Proceedings, 1971)
In general, the divers and their trainers are highly experienced, and there are many written works on training, amongst which "Diving" by Dr G. Eaves should be mentioned. The work which is now carried out makes for the first time measurement values available from diving. The take-off spring is the most important part of every dive. The impulse which is the physical base for the path of the trajectory and the correct measurement of the rotation were recorded with film and by electronical equipment. The tests were made with 3 subjects who were well experienced, if junior, divers from 14 - 16 years of age ; a girl weighing 48 kgs and two boys of 43 and 55 kgs respectively.